A Queer Economic Study: Exploring the Economic and Social Burden of Discrimination Against Black Lesbians in Johannesburg - Futshane, Vuyokazi (University of the Witwatersrand, Johannesburg, 2024)
This qualitative study explores the experiences of Black lesbians in Johannesburg, focusing on the intersections of their identity to understand the links between sexual orientation, discrimination, and the South African social and economic context. It examines the dynamics in the workplace and connects it to social relations outside of the workplace. Drawing upon intersectionality, this study reveals how race, class, gender, and sexual orientation do not operate independently but overlap simultaneously to shape Black lesbian’s experiences of discrimination. The findings highlight the varied nature of discrimination, ranging from subtle biases and microaggressions to overt forms of prejudice, and the strategic concealment of sexual orientation by some, a coping mechanism against potential biases. The study stresses the impacts of non-conformity of heteronormative expectations and underscores the importance of exploring queer economics to understand how identities intersect with socio-economic realities more comprehensively.
A Research Report submitted in partial fulfillment of the Degree of Master of Commerce (Inequality Studies) in the School of Economics and Finance, University of the Witwatersrand, Johannesburg 2024
Keywords: Black lesbians; Johannesburg; Intersectionality; Queer; Discrimination; Sexual Orientation; Identity; Socio-Economic; Experiences; Inequality; Inclusion; UCTD; SDG-8: Decent work and economic growth